Planejamento fatorial e superfície de resposta: otimização de um método voltamétrico para a determinação de ag(i) empregando um eletrodo de pasta de nanotubos de carbono - Fernando Campanhã Vicentini; Luiz Carlos Soares Figueiredo-Filho; Bruno C. Janegitz; Aline Santiago; Edenir Rodrigues Pereira-Filho; Orlando Fatibello-Filho (Química Nova, 2011)
A factorial design applied in a voltammetric stripping method for the measurement of Ag(I) in natural water is described. The procedure is based on the effective pre-concentration of silver ions on electrode surface. The calibration graph was linear in the silver concentration range from 7.92 x 10"7 to 1.07 x 10"5 mol L"1 with a detection limit of 3.81 x 10-7 mol L-1. The determination of Ag(I) in natural water samples was carried out satisfactory with the proposed electrode.